Reinventing Trust: Traditional Media Credibility and Audience Engagement in the Mobile-First Era - Tai, Chiun Hou; Mumtaz Aini Alivi (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The media landscape has undergone significant transformation due to the rapid development of digital technology. This has seriously threatened the legitimacy of traditional media. Given the emergence of new media platforms, this study investigated the variables affecting public confidence in traditional media. Using the uses and gratifications theory, the study examined how media audiences perceived news credibility, content quality, and technological adaptation. In-depth interviews with media professionals and regular news audiences revealed important themes pertaining to trust, bias, content depth, and audience engagement. The study provides insights into the necessity of digital transformation tactics to preserve audience trust, as well as the importance of fact-checking, investigative journalism, and balanced reporting in preserving credibility. The study also suggests ways to strengthen the position of traditional media in the digital information ecosystem.